An iliac-appendiceal fistula causing gastrointestinal bleeding - Gurien, Steven D. (J Vasc Surg Cases Innov Tech, 2019)
Aortoenteric fistulas are an uncommon cause of gastrointestinal bleeding, and iliac-appendiceal fistulas are an even rarer cause. We describe a case of an iliac-appendiceal fistula in a patient who presented several months after aortic reconstruction with gastrointestinal bleeding. An extensive workup revealed that the source of bleeding was localized to the appendiceal orifice. The patient underwent an appendectomy with a two-stage procedure involving the iliac graft for definitive repair and ultimately recovered well. Despite the rarity of aortoenteric and iliac-appendiceal fistulas causing gastrointestinal bleeding, keeping a high index of suspicion in patients with a prior vascular repair can prevent death.